PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), DAN NET PROFIT MARGIN (NPM) TERHADAP RETURN SAHAM PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Helmi Toatubun (JURNAL AKUNTANSI BARELANG, 2019)
This study explains the effect of Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) on Return of Food and Beverage Company Stock listed on Indonesia Stock Exchange. The purpose of this study is to prove empirically partially and simultaneously influence between Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) on Stock Return. Sample selection in this study using purposive sampling based on certain considerations and criteria. Methods of data analysis using multiple linear regression. The result of the research shows that partially return on asset (ROA) statistically has no effect on stock return, Return On Equity (ROE) statistically has positive and significant effect to stock return, and Net Profit Margin (NPM) variable has positive and significant influence to the stock return of food and beverage companies listed on the Indonesia Stock Exchange. While on simultaneous test by using F test, Return on Asset (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) get Fcount equal to 566,145 bigger than Ftable that is equal to 1,689 with significance value equal to 0.000 more small from 0.05, meaning that simultaneously have a positive and significant effect on stock return of food and beverage companies listed in Indonesia Stock Exchange.